The multiple faces of autoimmune Addison’s disease in children - Capalbo, Donatella; Esposito, Andrea; Gaeta, Valeria; Lorello, Paola; Vasaturo, Sara; Di Mase, Raffaella; Salerno, Mariacarolina (Frontiers in Endocrinology, 2024)
Primary adrenal insufficiency (PAI) is a rare medical condition, characterized by a deficiency in adrenal hormones. Although rare, PAI is a life-threatening disease requiring prompt recognition and treatment. However, symptoms of PAI are often non-specific and diagnosis can be challenging, causing frequent diagnostic delays. In adults, autoimmunity is the most common cause of PAI in industrialized countries, whereas in children, the most frequent etiology is represented by congenital defects of steroidogenesis and, in particular, by congenital adrenal hyperplasia (CAH) due to 21-hydroxylase deficiency. A few recent case series from different countries have reported that autoimmunity is the second most common etiology of PAI in the pediatric age group. However, data on autoimmune PAI in children are still scant and the exact epidemiology, clinical manifestations, and long-term outcomes of this condition have yet to be defined. The scope of this review is to summarize the current knowledge on the etiology, presentation, and treatment of autoimmune PAI in childhood and to increase physicians’ awareness of the signs that should raise an early suspicion of this condition.